Bio-Repository of DNA in stroke (BRAINS): A study protocol - Froguel Philippe; Bentley Paul; de Silva Ranil; Slark Julia; Khan Muhammad; Maheshwari Ankita; Schanz Renata; Yadav Sunaina; Kooner Jaspal; Shrivastav Padma; Prasad Kameshwar; Sharma Pankaj (BMC, 2011)
Abstract Background Stroke is one of the commonest causes of mortality in the world and anticipated to be an increasing burden to the developing world. Stroke has a genetic basis and identifying those genes may not only help us define the mechanisms that cause stroke but also identify novel therapeutic targets. However, large scale highly phenotyped DNA repositories are required in order for this to be achieved. Methods The proposed Bio-Repository of DNA in Stroke (BRAINS) will recruit all subtypes of stroke as well as controls from two different continents, Europe and Asia. Subjects recruited from the UK will include stroke patients of European ancestry as well as British South Asians. Stroke subjects from South Asia will be recruited from India and Sri Lanka. South Asian cases will also have control subjects recruited. Discussion We describe a study protocol to establish a large and highly characterized stroke biobank in those of European and South Asian descent. With different ethnic populations being recruited, BRAINS has the ability to compare and contrast genetic risk factors between those of differing ancestral descent as well as those who migrate into different environments.